2020
DOI: 10.14336/ad.2019.0320
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Sestrin2 in Cell Metabolism, and Cardiovascular and Age-Related Diseases

Abstract: Sestrins (Sesns), including Sesn1, Sesn2, and Sesn3, are cysteine sulfinyl reductases that play critical roles in the regulation of peroxide signaling and oxidant defense. Sesn2 is thought to regulate cell growth, metabolism, and survival response to various stresses, and act as a positive regulator of autophagy. The antioxidative and anti-aging roles of Sesn2 have been the focus of many recent studies. The role of Sesn2 in cellular metabolism and cardiovascular and age-related diseases must be analyzed and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 109 publications
(143 reference statements)
2
52
1
1
Order By: Relevance
“…Sestrins are highly conserved stress response proteins; the three sestrins (Sesn1–3) expressed in mammals are encoded by three independent genomic loci. Sestrins are mainly induced by hypoxia, oxidative stress, DNA damage, and other stress [ [26] , [27] , [28] , [29] ]; they have also been shown to mediate exercise benefits and adaptations in both fly and mouse models [ 30 ]. Recent studies have shown that Sesn2 can inhibit mTORC1 through 5′-adenosine monophosphate-activated protein kinase (AMPK)-dependent or -independent pathways [ 27 , 28 , [31] , [32] , [33] , [34] ].…”
Section: Introductionmentioning
confidence: 99%
“…Sestrins are highly conserved stress response proteins; the three sestrins (Sesn1–3) expressed in mammals are encoded by three independent genomic loci. Sestrins are mainly induced by hypoxia, oxidative stress, DNA damage, and other stress [ [26] , [27] , [28] , [29] ]; they have also been shown to mediate exercise benefits and adaptations in both fly and mouse models [ 30 ]. Recent studies have shown that Sesn2 can inhibit mTORC1 through 5′-adenosine monophosphate-activated protein kinase (AMPK)-dependent or -independent pathways [ 27 , 28 , [31] , [32] , [33] , [34] ].…”
Section: Introductionmentioning
confidence: 99%
“…Sestrin2 is suggested to be associated with aging and age-related diseases [ 10 , 11 ], and plasma sestrin2 levels were reported to positively correlate with age [ 12 , 17 ]. In our study, sestrin2 levels also correlated with age ( r = 0.29).…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is recognized to be associated with inflammation with oxidative stress [ 1 , 2 ], and sestrin2 is suggested to play a protective role against atherosclerotic disease [ 10 , 11 ]. Regarding the association between sestrin2 and atherosclerotic disease, one small study [ 12 ] recently reported that plasma sestrin2 levels were higher in 44 patients with stable CAD than in 35 patients without CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Aging or shortening of lifespan is closely connected with the exposure to oxidative stress, DNA damaging agents, losing immunity, and metabolic dysregulation (Lee et al, 2013;Wei Y. et al, 2015;Srivastava, 2017;Dalina et al, 2018;Fan et al, 2020;Sun et al, 2020). As human life expectancy has extended, the importance of healthy aging or elderly health is increasing and drawing significant attention among the general public.…”
Section: Sestrins In Environmental Stress and Agingmentioning
confidence: 99%